PENGARUH AKUNTABILITAS, KEJELASANSASARAN ANGGARAN DAN PARTISIPASIPENGANGGARAN PADA KINERJA MANAJERIAL DI SKPD KOTA DENPASAR - Wianti, I Gusti Putu Mira; Sisdyani, Eka Ardhani (E-Jurnal Akuntansi, 2016)
This study aims to empirically scrutinize the influence of accountability, budgetary target clarity and budgetary participation on managerial performances of government task units in Denpasar city. This research uses primary data obtained from the questionnaire. Population in this research was regional institution unit in Denpasar city. The sampling technique in this research was purposive sampling. Sample obtained as much as 140 respondents. Multiple linear regression analysis was used to analyze the data in this research. The results show that accountability, budgetary target clarity, and budgetary participation have a positive impact on the managerial performances of regional institution in Denpasar.
Keywords: Accountability, Budgetary Target Clarity, Budgetary Participation, Managerial Performances